Toward a Broader Understanding: A Formal Concept Analysis of the Micropolitics of a School - Kairienė, Aida (Acta Paedagogica Vilnensia, 2018)
[full article in English] The micropolitics of a school is one of the key factors that determine changes in member interactions in a learning organization and requires a careful study in order to create a favorable school environment. The aim of this study is to analyze the concept of the micropolitics of a school, highlighting the essential attributes of the concept. The research method – Formal Concept Analysis (FCA) – was used to identify the implicit relationships between objects described through a set of the attributes. The analysis of scientific literature reveals 6 sets of objects: micropolitics as a dimension of leadership; micropolitics as a part of macropolitics; micropolitics as a teacher’s life and actions; micropolitics as interactions within an organization; micropolitics as the daily life of an organization; micropolitics as the darker side of institutional life.